Analisis Sumber Informasi Bagi Petani dalam Budidaya Tanaman Ubi Jalar - Astuty Wunawarsih, Ima (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2012)
The purpose of this study are: 1) to determine the level of utilization of information resources of farmers in the cultivation of sweet potato crops,2) knowing the relationship between the identity of respondents to the level of utilization of information resources of farmers in the cultivation of sweet potato crops. The population in this study consisted of 123 farmers sampled the sweet potato and 20% of the population in order to obtain a sample of 25 respondents. Data were analyzed using descriptive qualitative, to determine the level of utilization of information resources of farmers in the cultivation of sweet potato crops and the interval formula used to determine the identity of the respondent's relationship with the utilization of information sources of farmers in the cultivation of sweet potato crops used Rank Spearman correlation formula. The results showed: 1 a. Farmers make use of information sources with a high category as many as 10 respondents (40%), there are eight categories of respondents (32%), low category contained seven respondents (28%), b. The sources of information utilized in the high category, namely from fellow farmers, contact farmers and PPL, the categories are derived from television and radio, low category comes from print media posters, brochures, and flyers (leaflets, folders, and pamphlets), 2. The relationship between the utilization of educational resources in farmers' sweet potato crop showed a significant relationship, farming experience showed a significant relationship, while age, the area of arable land, media ownership, and cosmopolitan significant showed no relationship.